2005
DOI: 10.1089/end.2005.19.68
|View full text |Cite
|
Sign up to set email alerts
|

Percutaneous Rheolytic Thrombectomy for Treatment of Acute Renal-Artery Thrombosis

Abstract: We propose the use of the AngioJet thrombectomy catheter for the percutaneous treatment of acute renal-artery thrombosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
15
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 8 publications
0
15
0
1
Order By: Relevance
“…Mechanical rheolytic thrombectomy has been used for treatment of acute limb ischemia, 25 pulmonary embolism, 26 deep venous thrombosis 27 and dialysis access complication. 28 As with our patient, percutaneous rheolytic thrombectomy using the AngioJet catheter has been used successfully by others to treat RAE and thrombosis [29][30][31] ( Table 2). The AngioJet thrombectomy device relies on a highpressure saline jet passing from the tip of catheter, then up the catheter shaft to the external system to create a low-pressure zone at the catheter tip to facilitate thrombus extraction.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Mechanical rheolytic thrombectomy has been used for treatment of acute limb ischemia, 25 pulmonary embolism, 26 deep venous thrombosis 27 and dialysis access complication. 28 As with our patient, percutaneous rheolytic thrombectomy using the AngioJet catheter has been used successfully by others to treat RAE and thrombosis [29][30][31] ( Table 2). The AngioJet thrombectomy device relies on a highpressure saline jet passing from the tip of catheter, then up the catheter shaft to the external system to create a low-pressure zone at the catheter tip to facilitate thrombus extraction.…”
Section: Discussionmentioning
confidence: 87%
“…Adjuvant procedures such as intra-arterial thrombolysis, balloon angioplasty, and renal artery stent have been used during percutaneous thrombectomy of RAE. [29][30][31] More recently, rheolytic pharmacomechanical thrombectomy has been used to successfully treat acute RAE. 32 Complications of endovascular treatment of RAE are reported to occur in up to 3% of cases 33 and include access site complications, distal embolization, arterial rupture, cardiac events, and death.…”
Section: Discussionmentioning
confidence: 99%
“…The AngioJet catheter for acute renal artery thrombosis was fi rst reported in 2002 with satisfactory results and no complication [4], which has also been applied for recent similar cases [3,7,8,14]. The most signifi cant advantage is quick restoration of blood fl ow to preserve renal function, but there exist some problems that should be for cautions, including potential hemolysis, hemoglobinuria, and distal embolization [15], although the procedure time by AngioJet catheter is concise due to the short lesion length of renal artery as in this case only 10 seconds.…”
Section: Discussionmentioning
confidence: 99%
“…The maximum duration of complete RAO beyond which thrombolysis would no longer be beneficial is not known. One study reported little benefit after several hours [13], while others noted some benefit up to several days later [14]. Later therapy is likely to be effective only with incomplete occlusion.…”
Section: Discussionmentioning
confidence: 99%